PENATALAKSANAAN FISIOTERAPI PADA KASUS DE QUERVAIN SYNDROM DEXTRA DENGAN MODALITAS ULTRASOUND, DEEP TRANSVERSE FRICTION DAN STRECHING DI RS KEBON JATI - Nurfadhilah, Ine; Rahman, Ika (Jurnal Infokes, 2023)
De Quervain Syndrom is Painful condition that affects the tendons in the thumb of the wrist, Repetitive hand or wrist movements can worsen the condition. To find out physiotherapy management in reducing pain, increasing joint range of motion, and restoring functional ability in cases of De Quervain Syndrome using Ultrasound (US), Deep Transverse Friction and Stretching modalities. After undergoing therapy 6 times, the result was a reduction in silent pain from T1:2 to T6:0, tender pain from T1:6 to T6:3, and movement pain from T1:5 to T6:2. Increased range of motion of flexion joints T1: 40◦ to T6: 50◦, Extension T1: 35◦ to T6: 45◦, Radial deviation T1: 10◦ to 15◦, Ulnar deviation T1: 20◦ to 25◦. Increased functional activity is indicated by a reduction in the WHDI score, namely T1: 30% to T6: 20%. In the case of De Quervain Syndrome, physiotherapy plays a very important role in optimizing the results of therapy, patients are advised to reduce/avoid repetitive activities such as cutting, squeezing and grinding. Ultrasound (US) can help reduce pain, Deep Transverse Friction and Stretching can help increase muscle strength and increase joint range of motion.